2008
DOI: 10.1007/s00435-007-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal development in larval mussel Mytilus trossulus (Mollusca: Bivalvia)

Abstract: Although our understanding of neuronal development in Trochozoa has progressed substantially in recent years, relatively little attention has been paid to the bivalve molluscs in this regard. In the present study, the development of FMRFamide-, serotonin-and catecholamine-containing cells in the mussel, Mytilus trossulus, was examined using immunocytochemical and histoXuorescent techniques. Neurogenesis starts during the trochophore stage at the apical extreme with the appearance of one FMRFamide-like immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(128 citation statements)
references
References 61 publications
13
114
0
1
Order By: Relevance
“…Current studies on molluscan development include many aspects such as cell fate mapping (Dictus and Damen, 1997;Hejnol et al, 2007), axis determination (Koop et al, 2007), organogenesis (Voronezhskaya et al, 2008;Wang et al, 2008) and shell formation (Nederbragt et al, 2002;Kin et al, 2009). Studies on these processes are essential to understand the development and evolution of mollusks.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on molluscan development include many aspects such as cell fate mapping (Dictus and Damen, 1997;Hejnol et al, 2007), axis determination (Koop et al, 2007), organogenesis (Voronezhskaya et al, 2008;Wang et al, 2008) and shell formation (Nederbragt et al, 2002;Kin et al, 2009). Studies on these processes are essential to understand the development and evolution of mollusks.…”
Section: Introductionmentioning
confidence: 99%
“…in the polyplacoporan Ischnochiton (Voronezhskaya et al 2002), the gastropods Ilyanassa and Crepidula (Dickinson and Croll 2003;Hejnol et al 2007) (see Fig. 8) and the bivalve Mytilus (Voronezhskaya et al 2008). Its function is poorly studied, but it is involved in settling in some species (Hadfield et al 2000).…”
Section: Molluscamentioning
confidence: 99%
“…It has been seen that the first 5-HT-IR neurons appearing within the nervous system correspond to the location of the CG and apical ganglion (AG) during the late trochophore stage: 30-32 h postfertilization in blue mussel [136], 24 h postfertilization in surf clam [137], and 27 h postfertilization in the Bay mussel (Mytilus trossulus) [138]. Kreiling et al [137] reported As animals lost the ability to synthesize tryptophan, there possess developed biological mechanisms through which animals obtain tryptophan from their diets.…”
Section: Conclusion and Future Research Perspectivesmentioning
confidence: 99%